Negative current collector, method for manufacturing the same, and sodium-ion battery without negative electrode
Patent Information
- Application Number
- CN202610904993.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-30
AI Technical Summary
但是在钠离子电池中,无负极体系主要面临以下几个核心问题:1.钠沉积不均匀问题,传统负极的嵌钠位点消失后,钠离子只能在集流体表面直接还原沉积,钠金属的沉积行为本身更难控制,易出现局部聚集、沉积不均的现象,形成钠枝晶前驱体
本发明的技术方案以Ag单原子作为催化底层,Ag纳米簇作为成核中间层以及Ag纳米线作为导电网络层。通过亲钠单原子 Ag 的界面催化作用与共价有机框架(COF)的结构优势结合,同时实现钠离子均匀沉积、钠枝晶抑制,克服了现有技术单一解决方案的局限性。 COF 的多位点聚合物结构大幅提高钠离子在负极表面的形核位点数量,单原子 Ag 的均匀分散性引导钠离子均匀沉积,避免局部钠金属聚集。
Smart Images

Figure CN123017979A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a negative electrode current collector and its preparation method, and a sodium-ion negative electrode-free battery. Background Technology
[0002] To overcome the energy density bottleneck of sodium-ion batteries, cell weight reduction has become a key breakthrough. Against this backdrop, the "negative electrode-free" structure has attracted much attention due to its ability to significantly reduce battery weight and increase energy density by eliminating the need for sodium-containing negative electrode active materials. However, in sodium-ion batteries, the negative electrode-free system mainly faces the following core problems: 1. Uneven sodium deposition: After the disappearance of sodium intercalation sites in traditional negative electrodes, sodium ions can only be directly reduced and deposited on the surface of the current collector. The deposition behavior of sodium metal is inherently more difficult to control, easily leading to local aggregation and uneven deposition, forming sodium dendrite precursors. 2. Sodium dendrite safety issues: The continuous growth of sodium dendrites can pierce the SEI film, causing direct contact and short circuits between the positive and negative electrodes, posing a significant safety threat. Simultaneously, sodium-ion batteries generate high heat during charging and discharging, making thermal management difficult and further amplifying the safety risks caused by dendrites. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings and defects of the prior art and to provide a negative electrode current collector, its preparation method, and a sodium-ion negative electrode-free battery.
[0004] To achieve the above objectives, this application adopts the following solution: A negative electrode current collector includes a foil and a composite coating disposed on the aluminum foil; the composite coating includes a bottom layer, an intermediate layer and a top layer from near the aluminum foil to far away from the aluminum foil; the bottom layer includes Ag@COF-Py, the intermediate layer includes Ag nanoclusters and the top layer includes Ag nanowires.
[0005] Ag@COF-Py is prepared by the following method: Ag(I)-pyridine-2-carboxaldehyde oxime complex is refluxed with COF-Py in acetonitrile for coordination and anchoring, and Ag@COF-Py is obtained after centrifugation and washing; preferably, the content of Ag in Ag@COF-Py is 1-3%.
[0006] The Ag(I)-pyridine-2-carboxaldehyde oxime complex is prepared by mixing pyridine-2-carboxaldehyde oxime ligand with silver(I) salt in an ethanol solution and reacting at room temperature; preferably, the silver(I) salt is silver nitrate; preferably, the molar ratio of pyridine-2-carboxaldehyde oxime ligand to silver(I) salt is (1-1.5):1; Preferably, COF-Py is prepared by reacting 1,3,5-trimethylresorcinol with hydrazine hydrate under acetic acid catalysis. Preferably, the molar ratio of 1,3,5-trimethylresorcinol to hydrazine hydrate is 2:(2-4); more preferably, it is 2:3; preferably, the reaction temperature is 120-180℃, more preferably 150℃.
[0007] Ag nanoclusters were prepared by a low-temperature chemical reduction method, which included the following steps: AgNO3 was dissolved in deionized water, glutathione was added, the pH was adjusted to 8.0 with alkali, NaBH4 was slowly added under ice bath, stirring was continued, and the resulting solution was purified by dialysis after the reaction was completed. Preferably, the molar ratio of AgNO3:glutathione:NaBH4 is 1:(1-2):(2-5); more preferably, it is 1:2:5. Preferably, the average particle size of the Ag nanoclusters is 1-10 nm; more preferably 1.5 nm.
[0008] Ag nanowires were prepared as follows: AgNO3 and PVP were dissolved in ethylene glycol, and CuCl2·2H2O was added as a control agent; after the reaction was completed, the nanowires were washed by centrifugation with acetone and redispersed in ethanol to obtain Ag nanowires. Preferably, the Ag nanowires have a diameter of 40 nm and a length of 10-20 μm; Preferably, the mass ratio of AgNO3 to PVP is 1:(0.5-2); more preferably, it is 1:1; preferably, the molecular weight of PVP is Mw=1,300,000.
[0009] The present invention also includes a method for preparing the negative electrode current collector, comprising the following steps: dissolving Ag@COF-Py, Ag nanoclusters and Ag nanowires in spinning solution base solution to obtain bottom spinning solution, middle spinning solution and surface spinning solution; electrospinning and depositing the bottom spinning solution, middle spinning solution and surface spinning solution on the surface of aluminum foil to obtain the negative electrode current collector.
[0010] The spinning solution base liquid includes polyacrylonitrile and N,N-dimethylformamide, with a concentration of 10-20%, preferably 12%; preferably, the mass ratio of Ag@COF-Py, Ag nanoclusters and Ag nanowires to the spinning solution base liquid is independently 1:(5-20); more preferably 1:10.
[0011] The electrospinning process parameters are as follows: voltage: bottom layer 15 kV, middle layer 10 kV, top layer 10 kV; injection rate: bottom layer 0.5 mL·h. -1 Intermediate layer 0.8 mL·h -1 0.8 mL·h on the surface -1Reception distance: bottom layer 15 cm, middle layer 18 cm, top layer 20 cm.
[0012] The present invention also includes a sodium-ion battery without a negative electrode, comprising the aforementioned negative electrode current collector, positive electrode, and electrolyte.
[0013] The cathode material comprises: a sodium-based cathode active material, a conductive agent, and a binder; preferably, the sodium-based cathode active material comprises NVPF or NaNi. 0.3 Fe 0.3 Mn 0.4 O2; the conductive agent includes VGCF; the binder includes PVDF; preferably, the mass ratio of sodium-based positive electrode active material, conductive agent and binder is 85:10:5; Preferably, the electrolyte comprises sodium hexafluorophosphate and a carbonate mixed solvent with a solute concentration of 1.0-1.2 mol / L; preferably, the carbonate mixed solvent is EC / DEC / EMC with a volume ratio of 1:1:1.
[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: The technical solution of this invention uses Ag single atoms as the catalytic substrate, Ag nanoclusters as the nucleation intermediate layer, and Ag nanowires as the conductive network layer. By combining the interfacial catalytic effect of sodium-loving single-atom Ag with the structural advantages of covalent organic frameworks (COFs), uniform sodium ion deposition and sodium dendrite suppression are simultaneously achieved, overcoming the limitations of existing single-solution technologies. The multi-site polymer structure of COFs significantly increases the number of nucleation sites for sodium ions on the negative electrode surface, and the uniform dispersion of single-atom Ag guides uniform sodium ion deposition, avoiding localized sodium metal aggregation.
[0015] The fibrous three-dimensional porous composite coating prepared by electrospinning provides ample space for sodium ion deposition, confining sodium metal deposition within the three-dimensional network. This structurally prevents sodium dendrites from piercing the electrolyte membrane, significantly improving battery safety. Simultaneously, the composite coating current collector prepared by electrospinning allows for precise control of process parameters (voltage, injection rate, and receiving distance), resulting in strong adhesion between the coating and the foil, making it suitable for industrial-scale production.
[0016] In summary, the negative electrode of this invention adopts a composite coating current collector with sodium-loving single-atom interface catalysis. By introducing sodium-loving single-atom Ag as a catalyst into a covalent organic framework and constructing a three-dimensional porous composite coating by electrospinning, the current collector achieves synergistic effects of corrosion prevention, uniform sodium ion deposition and sodium dendrite suppression, while also adapting to the transport characteristics of the electrolyte composite interface. Attached Figure Description Figure 1 This is a morphology diagram of the composite current collector prepared in Example 1 of the present invention. Detailed Implementation
[0017] The present invention will be further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Unless otherwise specified in this application, all percentage contents are mass percentage contents.
[0018] Example 1: 1. Preparation of Ag@COF-Py: 1,3,5-trimethylresorcinol (TFP, 42 mg, 0.2 mmol), hydrazine hydrate (15 mL, 0.3 mol), mesitylene (1 mL), 1,4-dioxane (1 mL), and glacial acetic acid (6 mmol, 0.2 mL) were added sequentially to a 10 mL Pyrex reaction tube. The tube was degassed under vacuum by repeated freeze-thaw cycles. After sealing, the tube was placed in an oven at 150 °C and heated at a constant temperature for 24 hours. After the reaction was completed, the product was washed three times by centrifugation with N,N-dimethylformamide (DMF), then washed once with anhydrous ethanol, and finally dried in a vacuum oven at 60 °C for 12 hours to obtain a reddish-brown COF powder.
[0019] The pyridine-2-carboxaldehyde oxime ligand and silver(I) salt (silver nitrate) were mixed in an ethanol solution at a molar ratio of 1.2:1 and reacted at room temperature to generate the Ag(I)-pyridine-2-carboxaldehyde oxime complex. Ag(I)-pyridine-2-carboxaldehyde oxime complex was refluxing and coordinating with COF in acetonitrile, and after centrifugation and washing, Ag single atom@COF-Py (Ag@COF-Py) composite material was obtained, with Ag content in Ag@COF-Py being 2wt%.
[0020] 2. Preparation of Ag nanoclusters: AgNO3 (0.1 mmol) was dissolved in 10 mL of deionized water using a low-temperature chemical reduction method. Glutathione (GSH, Ag:GSH molar ratio 1:2) was added, and the pH was adjusted to 8.0 with NaOH. NaBH4 (0.5 mmol, dissolved in 1 mL of water) was slowly added under ice bath conditions, and stirring was continued for 1 h. The resulting solution was purified by dialysis to obtain Ag nanoclusters (Ag NCs) with an average particle size of ≈1.5 nm.
[0021] 3. Polyol method synthesis: 0.5 g AgNO3 and 0.5 g PVP (Mw=1,300,000) were dissolved in 50 mL ethylene glycol and reacted in an oil bath at 160℃ for 1 h. A small amount of CuCl2·2H2O (10 μmol) was added as a control agent. After the reaction was completed, the nanowires were washed with acetone by centrifugation and redispersed in ethanol to obtain Ag nanowires (Ag NWs) with a diameter of about 40 nm and a length of 10~20 μm.
[0022] 4. Preparation of negative electrode current collector: A gradient coating is constructed by electrospinning layer by layer. Spinning solutions with different silver forms are prepared and spun sequentially to form a three-layer composite structure with a thickness ratio of 1:1:1.
[0023] Specifically, the following steps are included: Polyacrylonitrile (PAN, molecular weight 150,000) is completely dissolved in N,N-dimethylformamide (DMF), and magnetically stirred at room temperature for 6 hours until a uniform and transparent spinning base solution PAN with a mass concentration of 12% is formed; Subsequently, Ag@COF-Py, Ag nanoclusters, and Ag nanowires were added to the transparent spinning base solution PAN at a mass ratio of 10:1. The mixture was then magnetically stirred for 2 hours and ultrasonically dispersed for 30 minutes until uniform dispersion without significant agglomeration was achieved, resulting in three electrospinning suspensions: a bottom layer spinning solution, a middle layer spinning solution, and a top layer spinning solution. The prepared suspensions were then loaded into 10 mL syringes, fitted with metal needles (0.8 mm inner diameter), and used for electrospinning to prepare a three-layer composite coating current collector. The electrospinning process parameters were as follows: Voltage: 15 kV for the bottom layer, 10 kV for the middle layer, and 10 kV for the third layer; Injection rate: 0.5 mL / h for the bottom layer -1 Intermediate layer 0.8 mL·h -1 The third layer is 0.8 mL·h -1 ; Reception distance: 15 cm for the bottom layer, 18 cm for the middle layer, and 20 cm for the third layer; Receiving device: Clean aluminum foil (10μm thick); Environmental conditions: Temperature 25±2℃, Humidity 30±5% Under the above conditions, the spinning solution is stretched into nanofibers under the action of a high voltage electric field and deposited on the surface of aluminum foil to form a fibrous three-dimensional porous Ag / COF-PAN composite coating with a thickness of 5-8 μm, thus obtaining the composite coating negative electrode current collector 1 of the present invention. Figure 1 The image shows the morphology of the prepared composite current collector.
[0024] 5. The sodium metal battery without a negative electrode consists of a positive electrode, a composite-coated negative electrode current collector, and an electrolyte; Preparation of positive electrode sheet: Sodium-based positive electrode material: VGCF:PVDF = 85:10:5 is mixed, coated onto current collector, dried and rolled to obtain positive electrode sheet.
[0025] Electrolyte: A carbonate mixed solvent (EC / DEC / EMC, volume ratio 1:1:1) is used as the solvent, and sodium hexafluorophosphate (NaPF6) is used as the solute, with a solute concentration of 1.0 mol / L; Battery fabrication: The battery was assembled in a glove box, consisting of the positive electrode, composite-coated negative electrode current collector 1, and electrolyte. The battery was numbered 1. Battery 1 underwent charge-discharge cycle testing at 25°C and a current of 1C. The test data are shown in Table 1.
[0026] Example 2: The difference between Example 2 and Example 1 is that the Ag loading in Ag@COF-Py is controlled at 1wt%, and the composite coating negative electrode current collector is 2.
[0027] Example 3: The difference between Example 3 and Example 1 is that the Ag loading in Ag@COF-Py is controlled at 3wt%, and the composite coating negative electrode current collector is 3.
[0028] Example 4: The difference between Example 4 and Example 1 is that Example 4 does not include an intermediate layer (the thickness ratio of the bottom layer to the surface layer is 1.5:1.5), and the composite coating negative electrode current collector 4 is used.
[0029] Example 5: The difference between Example 5 and Example 1 is that Example 5 does not include the surface layer (the thickness ratio of the intermediate layer to the bottom layer is 1.5:1.5), and the composite coating negative electrode current collector 5.
[0030] Comparative Example 1: A sodium metal battery without a negative electrode, using pure aluminum foil as the negative electrode current collector.
[0031] Comparative Example 2: In the preparation of the bottom layer, no silver nanoparticles were added. COF-py was directly electrospun with PAN composite. The remaining preparation steps and process parameters were exactly the same as in Example 1, resulting in COF composite coated negative electrode current collector 6 and battery number 7. Battery 7 was subjected to charge-discharge cycle testing at 25°C and a current of 1C. The test data are shown in Table 1.
[0032] Comparative Example 3: The negative electrode current collector uses a carbon negative electrode.
[0033] Batteries were prepared according to the examples and comparative examples: Preparation of the positive electrode: NVPF:VGCF:PVDF = 85:10:5 by mass, mixed, coated onto carbon-coated aluminum foil for current collectors, dried, and rolled to obtain the positive electrode. Electrolyte: A carbonate-based mixed solvent (EC / DEC / EMC, volume ratio 1:1:1) was used as the solvent, and sodium hexafluorophosphate (NaPF6) was used as the solute at a concentration of 1.0 mol / L. Table 1 shows the performance results of the corresponding batteries.
[0034] Table 1
[0035] The results show that the negative electrode of this invention uses a composite coating current collector with sodium-loving single-atom interface catalysis. By introducing sodium-loving single-atom Ag as a catalyst into the covalent organic framework and constructing a three-dimensional porous composite coating by electrospinning, the current collector achieves synergistic effects of corrosion prevention, uniform sodium ion deposition and sodium dendrite suppression, while also adapting to the transport characteristics of the electrolyte composite interface.
[0036] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of the equivalents of the claims be included within the invention.
[0037] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A negative electrode current collector, characterized in that, The material includes a foil and a composite coating disposed on the aluminum foil; the composite coating includes a bottom layer, an intermediate layer and a top layer from near the aluminum foil to far away from the aluminum foil; the bottom layer includes Ag@COF-Py, the intermediate layer includes Ag nanoclusters and the top layer includes Ag nanowires.
2. The negative electrode current collector according to claim 1, characterized in that, Ag@COF-Py is prepared by the following method: Ag(I)-pyridine-2-carboxaldehyde oxime complex is refluxed with COF-Py in acetonitrile for coordination and anchoring, and Ag@COF-Py is obtained after centrifugation and washing; preferably, the content of Ag in Ag@COF-Py is 1-3%.
3. The negative electrode current collector according to claim 2, characterized in that, The Ag(I)-pyridine-2-carboxaldehyde oxime complex is prepared by mixing pyridine-2-carboxaldehyde oxime ligand with silver(I) salt in an ethanol solution and reacting at room temperature; preferably, the silver(I) salt is silver nitrate; preferably, the molar ratio of pyridine-2-carboxaldehyde oxime ligand to silver(I) salt is (1-1.5):1; Preferably, COF-Py is prepared by reacting 1,3,5-trimethylresorcinol with hydrazine hydrate under acetic acid catalysis. Preferably, the molar ratio of 1,3,5-trimethylresorcinol to hydrazine hydrate is 2:(2-4); more preferably, it is 2:3; preferably, the reaction temperature is 120-180℃, more preferably 150℃.
4. The negative electrode current collector according to claim 1, characterized in that, Ag nanoclusters were prepared by a low-temperature chemical reduction method, which included the following steps: AgNO3 was dissolved in deionized water, glutathione was added, the pH was adjusted to 8.0 with alkali, NaBH4 was slowly added under ice bath, stirring was continued, and the resulting solution was purified by dialysis after the reaction was completed. Preferably, the molar ratio of AgNO3:glutathione:NaBH4 is 1:(1-2):(2-5); more preferably, it is 1:2:
5. Preferably, the average particle size of the Ag nanoclusters is 1-10 nm; more preferably 1.5 nm.
5. The negative electrode current collector according to claim 1, characterized in that, Ag nanowires were prepared as follows: AgNO3 and PVP were dissolved in ethylene glycol, and CuCl2·2H2O was added as a control agent; after the reaction was completed, the nanowires were washed by centrifugation with acetone and redispersed in ethanol to obtain Ag nanowires. Preferably, the Ag nanowires have a diameter of 40 nm and a length of 10-20 μm; Preferably, the mass ratio of AgNO3 to PVP is 1:(0.5-2); more preferably, it is 1:1; preferably, the molecular weight of PVP is Mw=1,300,000.
6. A method for preparing the negative electrode current collector according to any one of claims 1-5, characterized in that, The process includes the following steps: dissolving Ag@COF-Py, Ag nanoclusters, and Ag nanowires in a spinning solution base to obtain a bottom spinning solution, an intermediate spinning solution, and a surface spinning solution; electrospinning and depositing the bottom spinning solution, intermediate spinning solution, and surface spinning solution onto an aluminum foil surface to obtain a negative current collector.
7. The preparation method according to claim 6, characterized in that, The spinning solution base includes polyacrylonitrile and N,N-dimethylformamide, with a concentration of 10-20%, preferably 12%; preferably, the mass ratio of Ag@COF-Py, Ag nanoclusters and Ag nanowires to the spinning solution base is independently 1:(5-20); more preferably 1:
10.
8. The preparation method according to claim 6, characterized in that, The electrospinning process parameters are as follows: voltage: bottom layer 15kV, middle layer 10kV, top layer 10kV; injection rate: bottom layer 0.5mL·h. -1 Intermediate layer 0.8 mL·h -1 0.8 mL·h on the surface -1 Reception distance: bottom layer 15 cm, middle layer 18 cm, top layer 20 cm.
9. A sodium-ion battery without a negative electrode, characterized in that, It includes the negative current collector, positive electrode, and electrolyte as described in any one of claims 1-5.
10. The sodium-ion negative electrodeless battery according to claim 9, characterized in that, The cathode material comprises: a sodium-based cathode active material, a conductive agent, and a binder; preferably, the sodium-based cathode active material comprises NVPF or NaNi. 0.3 Fe 0.3 Mn 0.4 O2; the conductive agent includes VGCF; the binder includes PVDF; preferably, the mass ratio of sodium-based positive electrode active material, conductive agent and binder is 85:10:5; Preferably, the electrolyte comprises sodium hexafluorophosphate and a carbonate mixed solvent with a solute concentration of 1.0-1.2 mol / L; preferably, the carbonate mixed solvent is EC / DEC / EMC with a volume ratio of 1:1:1.